COST BENEFIT ANALYSIS ANTARA PEMBELIAN ALAT CT-SCAN DENGAN ALAT LASER DIODA PHOTOCOAGULATOR DI RSD BALUNG JEMBER - Nuryadi Nuryadi; Yennike Tri Herawati; Rafida Triwardhani (Jurnal Ilmu Kesehatan Masyarakat, 2014)
Cost benefit analysis is an economic analysis that is used to evaluate economic resources usage so that the scarce economic resources can be used efficiently. In 2014, Balung General Hospital suggests some program to central government in order to support operational activity in Balung General Hospital. However, not all suggestions can be realized because the limitation of fund given by government. The purpose of the research is doing calculation of Cost benefit analysis between suggestion of CT-Scan device purchasing or suggestion of Laser dioda photocoagulator in Balung General Hospital of Jember. This research is quantitatif descriptive with analysis unit in Radiology Installation and Eye Poly. Based on the calculation of each step of Cost benefit analysis, we know that each suggestion has different Benefit-Cost Ratio (BCR) value where BCR value of Laser dioda photocoagulator device purchasing suggestion is 0,858 that is bigger than BCR value of CT-Scan device purchasing suggestion which is 0,078. Based on the BCR value, so the first prioritized suggestion is the Laser dioda photocoagulator that brings bigger benefit for Balung General Hospital of Jember.   Keywords: Cost Benefit Analysis, BCR (Benefit Cost Ratio), CT-Scan, Laser dioda photocoagulator